CHAQ2020 - Hope Bay - Plans and drawings - Westin, Jonathan; Almevik, Gunnar (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the drawings and plans created from data gathered at Hope Bay.

The drawing of the stone hut was carried out using traditional methods and is available both as pencil original and cleaned up ink drawing. The plans were produced using scan data from the Faro Focus m70 on January 22 and 24.

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar de ritningar och planer som skapades i Hoppets Vik.

Se den engelska beskrivningen för mer information.

Ritningen av stenhyddan skapades med hjälp av traditionella metoder och är tillgänglig både som originalskiss och renritad i bläck. Områdesplanen är skapad med hjälp av den skanningsdata som samlades in på den tjugoandra och tjugofjärde januari med en Faro Focus m70 skanner.
CHAQ2020 - Hoppets vik - Planer och ritningar
Keywords: Antarctica; Antarktis; Antarctic region; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; History and Archaeology; Historia och arkeologi